Il DGA: inquadramento e cura nel percorso residenziale - Fontanella, T.; Martinelli, D.; Valentini, F. (Mission - Open Access, 2023)
In community settings, the treatment of Gambling Disorder is based on a multidisciplinary approach, which takes into account the multidimensional aspects of addiction, which is treated from all points of view – medical, psychological, educational and social/family. The experience of the last 6 years of the Comunità Incontro Onlus has shown, both in individual and personalized treatment, and thanks to the therapeutic groups that out of 100 guests of the Structure, 32 gambling addicts were detected in the year 2022, of which 5 “pure” and 27 “non-pure”, i.e. multi-addicted to cocaine and alcohol, demonstrating how awareness of this problem is underestimated. From the study of the Comunità Incontro, it emerged that at the beginning of the path in the community, the difficulty in understanding the reported problem emerges, since the idea that “sooner or later you win” still exists. It is important to work on awareness, to understand each of the player’s perceptions and cognitive distortions. It is essential to work on personal acceptance of the pathology, on not fearing the judgment of the other, on the motivation for the treatment path. Group work proved to be important, as it starts from the experiences of the participants or from events that occurred in the previous days and tries to recognize the typical dynamics of gambling. The group experience has proved to be useful in allowing the participation of subjects with very low levels of awareness as well, since they are invited to compare themselves with the experiences of others without necessarily having to expose themselves personally. It has been shown that, thanks to community and individual and group therapeutic work, there is an increase in awareness, from admission to the following six months, but above all in the number of people who experience the ability to control impulse and reduce desire, as measured at admission, 6 months and 12 months after the start of the course, also with the aid of diagnostic tools.